The thermal performance of green roofs in the hot, humid microclimate - D’Souza, Umica Joyce (2012)
Green roofs can alleviate the heat island effect in cities, regulate building temperatures and provide a positive impact on the built environment. This thesis reviews the evidence of the environmental impact with and without green roofs in the hot, humid microclimate of the UAE and measures the thermal performance of using green roofs on a micro-scale urban ENVI-met model of the Dubai Marina. The parameters measured in this experiment include Surface Albedo, Exchange Coefficient of Heat, Mean Radiant Temperature (MRT), Relative Humidity (RH), Predicted Mean Vote (PMV) , Percentage of People Dissatisfied (PPD) and Wind Speed. Improvements in plant to air interaction were studied using ENVI-met to gauge the temperature variations of green roofs. A study conducted on June 21st at 1:00 pm and December 21st at 1:00 pm depicted changes in temperature due to the impact of green roofs between the two different times of the year. During the hot, humid month surface albedo, PMV and PPD were the predominant changes documented due to the impact of green roofs, however during the winter months changes in temperature such as, MRT and RH were clearly visible in the ENVI-met simulations. From the documented findings, green roofs have shown a marked improvement in the thermal comfort levels of the surrounding built environment.